Psychological Improvement of Straight Kick Ability Through Barrier Hop Training in UKM Pencak Silat - Misran, Misran; Cakrawijaya, Muhammad Hidayat; Sulaiman, Fitriyanti; Kairawan, Kairawan (EduPsyCouns: Journal of Education, Psychology and Counseling, 2024)
This study aims to determine the effect of barrier hops training on the results of pencak silat straight front kicks in male athletes at UKM Pencak Silat. The method used in this research is a quasi-experimental method, which means that only samples are treated. The research design used was One Group Pretest-Posttest Design. Sampling used a total population sampling technique with a sample size of 40 people. The research instrument was the entire sample performing the straight front kick test. From the results of data processing and analysis using the data normality test and hypothesis testing using the t test formula, it is clear that barrier hops training has an effect on increasing the results of pencak silat straight front kicks. This can be seen from the results of data analysis through calculating the t test formula with the calculated t criterion being greater than t table (5,515 ˃ 1.70) with a confidence level of 0.95 (α = 0.05) and the number of samples (N = 40), so the proposed hypothesis is accepted. Barrier hops training really has an influence on improving the results of pencak silat straight front kicks. Based on the results of research regarding the effect of barrier hops training, which is thought to have an influence on increasing the results of pencak silat front straight kicks, it turns out that it has a significant influence on the results of pencak silat front straight kicks in male athletes at UKM Pencak Silat in Makassar.